Sensorially accepted Mangifera indica and Myrciaria dubia yogurts with high ascorbic acid content - Barrios Renteria, Juan Carlos; Espinoza-Espinoza, Luis Alfredo; Valdiviezo-Marcelo, Jaime; Moreno-Quispe, Luz Arelis (Frontiers in Sustainable Food Systems, 2022)
Ascorbic acid deficiency has been associated with several health conditions. The objective of this study was to evaluate the content of ascorbic acid and the sensorial qualities of Mangifera indica and Myrciaria dubia yogurts. Four yogurt treatments were elaborated with different concentrations of these fruits (T1: 15% and 5%; T2: 15% and 10%; T3: 20% and 5% and T4: 20% and 10%) respectively, compared with a control treatment (CT: yogurt with 15% of Fragaria vesca). The ascorbic acid contents of the different treatments were determined by spectrophotometry, with values in the following order (T1: 63.2 mg/100 g; T2:114.3 mg/100 g; T3: 57.3 mg/100 g; T4: 115.1 and the control treatment CT:11.5 mg/100 g). The sensorial evaluation consisted of the application of a hedonic scale of 5 points (1: I dislike it very much; 2: I dislike it; 3: I neither like it nor dislike it; 4: I like it; 5: I like it a lot), results show evidence that the acidity level had a significant influence during the sensory evaluation. Treatment (T3) showed the greatest preference. The use of Mangifera indica and Myrciaria dubia in the treatments studied ensured ascorbic acid concentrations compared to the control treatment. This was significantly appreciated by consumers when the percentage of Myrciaria dubia was less than 10% of the total mass of the yogurt.